DEVELOPING A VALID AND EFFECTIVE ICT-BASED ISLAMIC EDUCATION LEARNING MODEL FOR SMA 4 KENDARI - Musthan, Zulkifly (Program Pascasarjana Universitas Negeri Makassar, 2015)
ABSTRACTThis study aimed at producing a valid and effective learning model of ICT based Islamic Education (PAI TIK Model) at a senior high school, SMAN 4 Kendari. The study used Research and Development Design proposed by Borg ad Gall with IC based analysis approach. Based on needs assessment, theoretical review, and relevant studies, the initial model was developed. Expert validation technique is used to test the validity of the model. The model was then tested on a limited basis. The first trial found that the model of PAI TIK was applicable but less effective since both the standard and studentsâ activities have not met the criteria. The model was revised and the second test was conducted. The second trial showed that the model was effective because the studentsâ accomplishment met the criteria and the expected studentsâ activities had been achieved. It was also found that teacherâs ability to manage learning and studentsâ response towards learning is in positive category. Therefore, an effective and valid PAI TIK Model is obtained.